2020
DOI: 10.3389/fpsyg.2020.599913
|View full text |Cite
|
Sign up to set email alerts
|

ME-Work: Development and Validation of a Modular Meaning in Work Inventory

Abstract: As research on meaning in work progresses, access to theoretically integrated, differentiated survey instruments becomes crucial. In response to this demand, the present article introduces ME-Work, a modular inventory to measure meaning in work. Derived from research findings on meaning in life, the ME-Work inventory offers three modules that can be used separately or jointly. Module 1 assesses four facets of meaning in work, i.e., coherence, significance, purpose and belonging; module 2 measures the subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 100 publications
1
21
0
2
Order By: Relevance
“…Research confirmed positive relations of meaningfulness with work engagement, commitment, job and life satisfaction and health (Allan et al, 2019), as well as a positive relationship between organizational identification with job attitudes and behaviours (Lee et al, 2015). While experiences of meaning and identification could be important resources to cope with stressors (Schnell and Hoffmann, 2020), such experiences may also foster exploitative practices as live-in care workers' commitment and involvement may drive them to invest excess effort in their work, possibly carrying out other tasks (e.g. domestic work).…”
Section: The Study Framework: Five Dimensions Of Work-related Precari...mentioning
confidence: 73%
See 1 more Smart Citation
“…Research confirmed positive relations of meaningfulness with work engagement, commitment, job and life satisfaction and health (Allan et al, 2019), as well as a positive relationship between organizational identification with job attitudes and behaviours (Lee et al, 2015). While experiences of meaning and identification could be important resources to cope with stressors (Schnell and Hoffmann, 2020), such experiences may also foster exploitative practices as live-in care workers' commitment and involvement may drive them to invest excess effort in their work, possibly carrying out other tasks (e.g. domestic work).…”
Section: The Study Framework: Five Dimensions Of Work-related Precari...mentioning
confidence: 73%
“…The meaningful-subject-related dimension covers meaningfulness and fulfilment experienced at and through work, as well as the degree employees identify with a particular employment or work activity. According to Schnell and Hoffmann (2020), meaning in work comprises coherence, significance, purpose and belonging. Latent benefits of work (collective purpose, in this case; Jahoda, 1981) contribute to experiences of meaning.…”
Section: The Study Framework: Five Dimensions Of Work-related Precari...mentioning
confidence: 99%
“…This conclusion was basically consistent with Liu et al (2013) . Recently, some scholars have paid attention to the modular meaning and mediating role of meaningfulness of work ( Landells and Albrecht, 2019 ; Schnell and Hoffmann, 2020 ). However, they did not discuss the role of meaningfulness of work between leadership style and employee proactive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Data were obtained through a longitudinal survey administered online to workers of 6 organizations belonging the Veneto region in two different temporal sessions, one month apart. They investigated (a) the level of quality at work considering the dimensions of training, safety and communication at work, and (b) the construct Meaningful Work and related dimensions for the modules (1) facets of meaning in work (i.e., coherence, significance, purpose and belonging; (2) Meaning and crisis of meaning at work; (d) Work as a Source of Meaning (Schnell & Hoffmann, 2020;Tommasi et al, 2021). Participants initially recruited were 145, but 17 of them did not complete the questionnaire; then, because of several missing data in the returned questionnaires, 128 participants (56,3 % females, n = 72, average age µ = 37 years, σ = 12,3) constitute the final sample of this study.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Considering this, the study aims to analyse how the quality of work is perceived by employees in pandemic times, e.g., if there is a perceived worsening quality of work as a result of the implementation of anti-covid rules, if there is a proper level of health protection at work, if employees develop higher or lower sense of work changing their way of perceive it with regard to the type of contribution it can make or its usefulness. It is also interesting to look at whether the dimensions that are considered to be sources of meaning for workers (coherence, significance, purpose and belonging) also change at organizational level (Schnell & Hoffmann, 2020;Tommasi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%